A novel blue fluorescent polymer for solution-processed fluorescent–phosphorescent hybrid WOLEDs. Issue 12 (10th February 2015) - Wang, Jinshan; Xu, Xinjun; Tian, Yuan; Yao, Chuang; Liu, Ronghua; Li, Lidong
Abstract : Blue-emitting polymers with small singlet–triplet splitting (Δ E ST < 0.5 eV) as host materials for solution-processed fluorescent–phosphorescent hybrid WOLEDs were achieved. Abstract : Two blue-emitting fluorescent polymers PTPATPPO and PTPATPP with small singlet–triplet splitting comprising triphenylamine and triphenylphosphine/triphenylphosphine oxide moieties have been designed and synthesized. An appropriate overlap between the HOMO and the LUMO in these compounds was realized. This design strategy endows the two blue-emitting polymers with a high triplet energy of 2.45 and 2.46 eV, a shallow HOMO level of −5.21 and −5.23 eV, and a bipolar feature to act as good host materials. Monochromic organic light-emitting devices (OLEDs) using these polymers as emitters show sky-blue emissions with Commission Internationale de l'Eclairage (CIE) coordinates of (0.24, 0.32) and (0.24, 0.31) together with a maximum current efficiency of 3.63 cd A −1 . Moreover, the single-emitting-layer two-element fluorescent–phosphorescent (F–P) hybrid white OLEDs based on PTPATPPO or PTPATPP as both hosts and blue-emitting fluorophores were fabricated by a solution process. Among the two polymers, PTPATPPO-based F–P hybrid white OLEDs show better performance with a maximum current efficiency of 10.5 cd A −1, a maximum external quantum efficiency of 6.1%, CIE coordinates of (0.40, 0.34), and a maximum luminance of 11 962 cd m −2 .